Tissamaharama Pottery sequence and the Early Historic maritime Silk Route across the Indian Ocean - Schenk, Heidrun (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
Tissamaharama pottery sequence represents the regional development of pottery manufactured from 5th century B. C. E. to 12th / 13th century C. E. in Sri Lanka. The results reach beyond the island and include new perspectives on pottery that came from the Roman Empire, Mesopotamia, Northern India, Southeast Asia and China and distinctly illustrates cross-continental relations in the Indian Ocean region of Early Historic Period. A short overview is given here, but main focus is the Pre-Periplus maritime connection based on the evaluation of “Fine Grey Pottery from Northern India” at Tissamaharama. Their find spots trace Indian Ocean maritime routes as physical evidence in Pre-Roman times, which cover Southeast Asia differently to the picture drawn by the later Periplus. Earliest fi nds of this pottery group confi rm connections along the East Coast of India already in the 5th / 4th century B. C. Trans-continental routing across the Indian Ocean is then evidenced by finds like the well-known “Rouletted Ware” in the 2nd century B. C. It is suggested that they were transported from ports in the South of the Subcontinent. There, an emporium had formed in the course of time because favourable sailing conditions allow direct contacts of Western and Eastern Indian Ocean. The finds of “Fine Grey Pottery” in Southeast Asia evidence an earlier formation of the Eastern maritime network. To facilitate further research and to prevent the further use of misleading denominations, a draft of chronology and a new typology of “Fine Grey Pottery from Northern India” are proposed here. The southern made “imitation” of the dish with beaked rim (often mistaken for true “Rouletted Ware”) will be once more described and proposed as an important key type to prove the actual ports of embarkation.The article will be available as a PDF in the near future.